Dra. C. Jolan Bánóczy (1929-2016) - Miranda Tarragó, Josefa Dolores; Rodríguez Pérez, Irene; Martínez Brito, Isabel (Revista Cubana de Estomatología, 2017)
On Wednesday, August 31, 2016, Dr. Dra. C. Jolan Bánóczy, a great loss to the World Stomatology, died at the age of 87. He was born in Hungary on March 2, 1929. He graduated from the University Semmelweis, Budapest, Hungary, Doctor of Medicine in 1953, because the School of Dentistry opened its doors just in that year. His dedication to study and research led him to receive in 1956 his diploma of Doctor in Medical Sciences and already in 1968 he defended his thesis "Keratinization of the oral mucosa in physiological and pathological circumstances" to receive the degree of Doctor in Sciences (1978) with the theme "Clinical-pathological significance of oral leukoplakia." His scientific activity covered three aspects. For 25 years he investigated precancerous lesions together with the precancerosis group of the World Health Organization, led by Professor Jens Pindborg. He determined the clinical, histological and ultrastructural characteristics of buccal leukoplakia and carried out the largest follow-up study in that entity. He published the book "Oral leukoplakia" and about 80 scientific articles on the subject, many in international journals, among which there are five with Cuban authors. The second slope began in 1970; is dedicated for 30 years to the study of the etiology and prevention of dental caries; publishes articles referring to the clinical-epidemiological, microbiological and structural changes of enamel. It also investigates with Finnish collaboration the reducing effect of xylitol on dental caries. Follow-up studies demonstrated the considerable reduction of caries in Hungarian children by the consumption of fluoridated milk made in collaboration with the Borrow Foundation, of which she was president for several years. The third aspect is related to the teaching of Stomatology, in which it strived to achieve the harmonization of the training of future professionals in Europe promoting curricular changes; In this regard he made numerous publications and gave lectures throughout the world. She was vice president of the European Organization for Caries Dental Research (ORCA) and organized the ORCA Congress in Budapest and five national dental congresses with international participation. She was recognized as an honorary member of several institutions. On his last visit to Cuba (2008), he received the title of Honorary Member of the Cuban Society of Stomatology from its president Dr. C. Estela Gispert Abreu. The School of Stomatology of Havana organized a tribute and distinguished her with a well-deserved recognition of her career. He published more than 370 articles, numerous abstracts, 2 monographs and about 30 book chapters, he gave 400 lectures all over the world. Advised 6 scientific degrees, among which is the thesis of Doctor in Medical Sciences "Oral leukoplakia: epidemiological study in the City of Havana, Cuba and some histopathological aspects", by Dr. Irene Rodríguez Pérez. Since then, links of scientific collaboration with the Institute of Basic and Preclinical Sciences Victoria de Girón and the School of Stomatology of Havana were established; During this project he also exchanged with doctors Julio C. Santana Garay, Joaquin Urbizo Velez and Josefa Dolores Miranda Tarragó, which brought as a consequence a close scientific relationship and the emergence of undying ties of friendship and affection. The stomatology has said goodbye to an excellent professional, outstanding scientist, incomparable pedagogue, but above all to a human being who radiated wisdom, simplicity and love. It will remain in the memory of those who admired him and will recognize forever his dedication to the research and advance of Stomatology in the world. We express our condolences to your son Dr. Miklos Pal and thank him for the kindness of sending us the biographical information.